2003
DOI: 10.1088/0957-4484/15/1/025
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of single-crystalline silicon nanowires using molten gallium and silane plasma

Abstract: We report the first ever demonstration of using silane directly in the gas phase and molten gallium in a microwave plasma for bulk nucleation and growth of single-crystal quality silicon nanowires. Multiple nanowires nucleated and grew from micron- to millimetre-sized gallium droplets. The resulting nanowires were tens to hundreds of nanometres in diameter and were tens to hundreds of microns long. Transmission electron microscopy results confirmed the nanowires to be single crystalline, devoid of structural d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 14 publications
2
77
0
1
Order By: Relevance
“…In order to determine the doping concentration, electronic transport measurements should be realized. Preliminary studies corroborate the potential of gallium as a catalyst for the synthesis of silicon nanowires [26,27,31,32]. As an example, extensive carpets of nanowires have been realized by exposing a gallium coated silicon wafer to high power hydrogen plasma [31].…”
Section: Introductionmentioning
confidence: 68%
“…In order to determine the doping concentration, electronic transport measurements should be realized. Preliminary studies corroborate the potential of gallium as a catalyst for the synthesis of silicon nanowires [26,27,31,32]. As an example, extensive carpets of nanowires have been realized by exposing a gallium coated silicon wafer to high power hydrogen plasma [31].…”
Section: Introductionmentioning
confidence: 68%
“…[37][38][39][40] By means of a plasma in the nanowire growth reactor, the silicon precursor, silane in most cases, is partially precracked.…”
Section: Low Temperature Chemical Vapor Depositionmentioning
confidence: 99%
“…Growth with Ga 37,39,93,99,107 and In 40,93,100,107,108 is possible but only by applying rather harsh growth conditions. This is also true for Si nanowire growth using Bi, 57 despite its low surface tension of about 0.4 J m -2 .…”
Section: Surface Tension Criterionmentioning
confidence: 99%
“…In addition, by FTIR investigations on the intermediate products, it is revealed that the surfactants do volatilize gradually instead of burning out soon in the annealing process. These evidences strongly imply that the "annealing growth" mechanisms as Ostwald ripening [27,28] are more suitable for our PT nanorods than the "cooling growth" mechanisms as VLS theory [29]. Thus, we suggest that formation of nanorods should be attributed to three parts of modified assembling, recrystallizing and oriented attaching growth, as the schematic diagram depicted in Fig 6c. Since the PT nanorods are formed by the point-initiated uniaxial crystal growth, the lattice of them will be rigidly arrested from expansion [26,30,31].…”
Section: Resultsmentioning
confidence: 69%